Conceptualizing and Operationalizing Collaboration Among Multiple Caregivers of Older Adults. (21st November 2022) - Ellis, Katrina R; Koumoutzis, Athena; Lewis, Jordan P; Lin, Zhiyong; Zhou, Yuanjin; Chopik, William J; Gonzalez, Richard
Abstract: Objectives: In many families, multiple caregivers support older adults living with dementia. Studying collaboration among caregivers requires consideration of conceptual and methodological issues that have not been fully explored. This study presents a framework for conceptualizing caregiver collaboration and an index that captures variation in collaboration among multiple caregivers within care networks. Methods: We used data from the 2015 waves of the National Health and Aging Trends Study and National Study of Caregiving (NSOC) to operationalize collaboration among multiple caregivers ( N = 1, 298) of 552 care recipients ( M age = 83.69, SD = 7.73; 71.6% women; 47.9% possible/probable dementia; 38.9% people of color). Results: The care collaboration index considered individual and overlapping contributions while controlling for the size of the care network (caregivers in network responding to NSOC survey) and total network size (number of caregivers in network) in the statistical model. Larger care networks enabled more collaboration, both in general and across most types of tasks (βs > 0.38). Collaboration was greater among those caring for a Black or Hispanic care recipient, both in general and for household and medical/health tasks specifically (βs > 0.11). Collaboration was also greater among those caring for recipients with probable dementia, both in general and for most tasks (βs > 0.11) but not transportation-related tasks ( p = .219). Discussion: Results are examined in the context of care network dynamics and proposed mechanisms linking care collaboration to outcomes for caregivers and recipients. Strengths and limitations of our conceptualization and operationalization of collaboration are discussed.